Ethnomedicinal Asteraceae of Fez–Meknes: Therapeutic diversity, preparation practices, and Consensus-Based Knowledge - Ziani, Achraf; Ousaaid, Driss; Tahraoui, Adel; Elarabi, Ilham (Ethnobotany Research and Applications, 2026)
Background: The Fez–Meknes region in Morocco possesses considerable biocultural diversity and a long-established use of herbal medicine, wherein Asteraceae species hold significant ethnopharmacological value. Although various studies have been conducted, a consolidated, quantitative report on the applications, preparations, and community consensus surrounding Asteraceae in this area is still required. Methods: The present research documents the medicinal role of Asteraceae species in the Fez–Meknes region of Morocco. A total of ten culturally prominent taxa were identified through a systematic selection pipeline, after which FPIC-based interviews were conducted with 193 informants. Data were analyzed quantitatively using established ethnobotanical indices. Results: The study designated Matricaria chamomilla as the prominent species (UR=225; CSI=32.00), exhibiting 16 applications across metabolic, external, respiratory, dermatological, and general health categories. Artemisia herba-alba (CSI=36.26; UR=136) and Artemisia absinthium (CSI=27.20; UR=90) also showed broad therapeutic efficacy, particularly for gastrointestinal and metabolic ailments. Informant consensus was notably high for ICPC categories 'External causes' and 'Endocrine/Metabolic' (ICF=0.96), and strong for 'Respiratory', 'General', and 'Skin' (ICF=0.93–0.95). Rank-order analysis positioned M. chamomilla (ROP=84.06) and Anacyclus pyrethrum (ROP=83.33) as key species for pharmacological validation and conservation. Reduced present-day utilization of Dittrichia viscosa and Achillea millefolium, when contrasted with prior reports, may reflect transformations in the transmission of ethnomedical knowledge and treatment preferences. Conclusions: The results confirm the centrality of Asteraceae, highlight prioritized species, and call for the incorporation of rural and elder knowledge, together with longitudinal, ecological, and clinical approaches, to sustain biocultural resilience and ensure culturally appropriate primary healthcare. Keywords: Ethnobotanical survey, Asteraceae, Medicinal plants, Traditional medicine, Ethnobotanical indices, Fes-Meknes region, Morocco.